Transforming Education: How Teacher Performance Management and Appreciative Inquiry Leadership Improve Learning Quality - Dewi Nur Laksmi Astutiningtyas; Widya Kusumaningsih; Nurkolis Nurkolis (AL-ISHLAH: Jurnal Pendidikan, 2025)
Learning quality remains a fundamental aspect of strengthening Indonesia’s education system. Despite ongoing efforts, the 2023 Education Report revealed a decline in learning quality across 13 public elementary schools in Singorojo District, Kendal Regency, Central Java. This study responds to that issue by analyzing the impact of the Teacher Performance Management feature and the Appreciative Inquiry Leadership approach, both implemented in 2024, on improving learning quality. Employing a quantitative, causal-comparative research design, the study involved 103 teachers selected through proportional random sampling and utilized multiple linear regression analysis to explore the relationships among the variables. The findings suggest that both Teacher Performance Management and Appreciative Inquiry Leadership significantly contribute to enhanced learning quality when applied simultaneously. The results highlight the importance of integrating structured performance management with leadership that fosters appreciation, collaboration, and innovation. This study addresses a research gap by examining the joint effect of Teacher Performance Management and Appreciative Inquiry Leadership on learning outcomes in public elementary schools, a topic that remains underexplored in current literature. The practical significance lies in guiding educational leaders and policymakers to adopt strategies that nurture professional growth and create adaptive learning environments tailored to students’ needs.